Biosequestration of carbon dioxide, biomass, calorific value and biodiesel precursors production using a novel flask culture photobioreactor. (January 2015) - Fulke, Abhay B.; Krishnamurthi, K.; Giripunje, Manisha D.; Devi, S. Saravana; Chakrabarti, Tapan
Abstract: Renewable, carbon neutral, economically viable alternative fuels are urgently needed to turn away the consequences of climate change. Photosynthetic capability of microalgae with respect to CO2 fixation at various CO2 partial pressures generated by CO2 generating buffer (KHCO3 /K2 CO3 ), increases in biodiesel precursors using IR-CO2 sensor and modern LED lights-based modern two tier flask photobioreactor has been studied. Chlorella vulgaris and Scenesdesmus obliquus were found to produce 37.11% and 32.23% of palmitic acid (C16:0) and 30.88% and 39.73% of octadecenoic acid (C18:1) of total fatty acid methyl esters (FAMEs) respectively at 7.5% of CO2 partial pressure, under the optimal values for growth. Carbon dioxide fixation rate, efficiency of conversion of biomass to calorific value and biodiesel precursors were also estimated. Graphical abstract: Highlights: Novel IR-CO2 sensor & LED-based flask culture photobioreactor. Growth of microalgae under a differential CO2 partial pressure generated by buffer. CO2 fixation rate, biomass, calorific value and biodiesel precursors of microalgae were measured.